DNA processing in conjugative transfer - Schildbach, Joel (Henry Stewart Talks, 2008)
Conjugative plasmids, Original observation of conjugative transfer, Description of transfer, DNA specificity in conjugative transfer, F transfer as an example, Roles of F proteins in transfer, Context dependence of F TraI recognition as regulation